2022
DOI: 10.1038/s41598-022-23751-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of low intensity visible light on human keratinocytes using a customized LED exposure system

Abstract: Photobiomodulation (PBM) refers to the use of light to modulate cellular processes, and has demonstrated utility in improving wound healing outcomes, and reducing pain and inflammation. Despite the potential benefits of PBM, the precise molecular mechanisms through which it influences cell behavior are not yet well understood. Inconsistent reporting of key light parameters has created uncertainty around optimal exposure profiles. In addition, very low intensities of light, < 0.1 J/cm2, have not been thoroug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…As the scratch assay experiments were performed in reduced FBS (1%) compared, it can be concluded that the scratch wound model's closure is influenced by another factor, possibly keratinocyte migration. This hypothesis is further supported by the work of Sutterby [ 24 ] and Sperandio [ 25 ], suggesting the role of red light on cell migration. Although the two experiments, proliferation and scratch assay, were performed with different FBS supplementations and can not be directly compared, we can assume that in a real wound, low-power laser light will contribute to wound closure by both proliferation and migration.…”
Section: Discussionsupporting
confidence: 56%
“…As the scratch assay experiments were performed in reduced FBS (1%) compared, it can be concluded that the scratch wound model's closure is influenced by another factor, possibly keratinocyte migration. This hypothesis is further supported by the work of Sutterby [ 24 ] and Sperandio [ 25 ], suggesting the role of red light on cell migration. Although the two experiments, proliferation and scratch assay, were performed with different FBS supplementations and can not be directly compared, we can assume that in a real wound, low-power laser light will contribute to wound closure by both proliferation and migration.…”
Section: Discussionsupporting
confidence: 56%
“…This stimulation may be caused by exposure to low‐intensity visible light, which has been shown to stimulate cell metabolism in a range of cell types. [ 49,50 ] Nevertheless, the relatively stable metabolic activity observed across culture in most groups was expected as adipose tissue largely contains terminally‐differentiated adipocytes, which undergo minimal proliferation in this state. [ 51,52 ] Despite this, the DNA‐content of the collagen‐encapsulated controls increased over culture; while the low photocross‐linking intensities slowly reduced with large decreases observed at high cross‐linking intensities (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, blue light alone decreased ROS levels in HaCaT cells, suggesting a potential cell-protective effect of blue light in certain cell types. Sutterby et al demonstrated that monochromatic visible light (yellow, orange, and red light) induces proliferation and wound healing in HaCaT cells [29]. The effect of blue light was not assessed, thus this question requires further investigation.…”
Section: Discussionmentioning
confidence: 99%